1988
DOI: 10.2165/00003495-198836010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Enoxacin

Abstract: Enoxacin is a new addition to the class of 4-quinolone antibacterial drugs. It has a broad spectrum of in vitro antibacterial activity, and is particularly potent against Gram-negative organisms and staphylococci. The pharmacokinetic profile of enoxacin is similar to that of ofloxacin, achieving higher plasma and tissue concentrations and possessing a longer half-life than norfloxacin or ciprofloxacin. In comparative studies, clinical and/or bacteriological efficacy was comparable or (in studies which statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…To date we have focused our attention primarily on enoxacin, which is a second generation fluoroquinolone antibiotic [99]. It was used in the United States for about ten years for the treatment of urinary tract infections and gonorrhea, and was voluntarily taken from the market in the US because of adverse effects including insomnia [100].…”
Section: Introductionmentioning
confidence: 99%
“…To date we have focused our attention primarily on enoxacin, which is a second generation fluoroquinolone antibiotic [99]. It was used in the United States for about ten years for the treatment of urinary tract infections and gonorrhea, and was voluntarily taken from the market in the US because of adverse effects including insomnia [100].…”
Section: Introductionmentioning
confidence: 99%
“…Lomefloxacin exhibits antibacterial activity against a wide range of Gram-negative bacteria [15,16]. Similarly, Enoxacin also exhibits activity against Gram-negative bacteria, but shows comparatively lower efficacy against Gram-positive microorganisms [17,18]. The comprehensive examination of ADMET properties and binding energy analysis indicated that acyl transferases LpxA and LpxD exhibited a particular preference for fluoroquinolones.…”
Section: Toxicity and Adme Screeningmentioning
confidence: 99%
“…Enoxacin, an antibacterial agent used for treating urinary tract infections [55], has previously been identified as a radioprotector. Using a high-throughput screening method with viability of lymphocytes as the primary readout, two classes of antibiotics (tetracyclines and fluoroquinolones) were identified as robust radioprotectors, including enoxacin [56].…”
Section: Drug Downselection Processmentioning
confidence: 99%